Part 4: Developing intercultural competence in Seville outside the classroom. Issue 3 (1st December 2019) - Infante Mora, Eva; Álvarez-Ossorio Piñero, Luisa; Miranda Díaz, Bartolomé
Abstract : This section of the comprehensive account of the action research and pedagogical reform of the CASA-Sevilla study-abroad programme concerns the introduction of community-engaged learning as a way to complement classroom instruction. Some experiential elements were already part of the programme's previous design (homestays, cultural visits), but they needed to be structured into the curriculum, with clear learning goals and evaluation criteria. In addition, to palliate the obstacles students experienced when trying to establish connections with the local society, service-learning in community organisations was introduced into the core 'Beyond Stereotypes' course. This section describes the strategies that were designed to encourage active learning in the homestays, the cultural visits and the participation in community organisations, and the role these elements play in the new programme.